Synchronous bio-degradation and bio-electricity generation in a Microbial Fuel Cell with aged and fresh leachate from the identical subtropical area. (15th August 2022) - Cheng, Peng; Shan, Rui; Yuan, Hao-Ran; Tan, Xiangping; Chen, Yong; Wu, Jinchuan
Abstract: Seasonal leachate from both sealed and operating landfill in the identical district were employed as the sole substrate in the Microbial Fuel Cell (MFC) to evaluate the power output performance and aqueous organic waste disposal. The electrical performance was characterized to study the power generation, while the Chemical Oxygen Demand (COD) removal ratio and Coulombic Efficiency (CE) were calculated to illustrate the substrate disposal effect. In addition, Scanning Electron Microscope (SEM) on the operated anode was conducted to preliminarily explain the microbial community difference, and the phylogenetic tree constructed on the cultivated microorganism was an insight into the dominant bacteria suitable for leachate degradation. It was found that the MFCs inoculated with seasonal leachate from both sealed and operating landfill could generate electricity successfully. Although the fresh leachate-inoculated MFCs had better electrical output performance (22.7–25.6 W/m 3 versus 6.61–7.48 W/m 3 ) and COD removal efficiency (55.8%∼61.7% versus 47.7%∼51.4%), the CEs were only 4.3%∼7.6%, which were lower than the aged leachate inoculated group (5.9%∼11.3%). Based on the SEM images and the phylogenetic tree of the operated anode, the composition impacts on the microbial community and power output performance were verified, which was instructive for the leachate disposal in the MFC. Highlights: Seasonal leachate of both fresh and aged in the identical district were employed. Region and source of the leachate were controlled to study the component effect. Regularity of leachate composition on the MFC's performance was hypothesized. Influence of component on the microbial activity were reflected on phylogeny tree.